Determinants of tourism demand in Tipaza (Algeria) - Tayeb, Mokrani; Rachid, Zahali; Walid, Touahria (The International tax journal, 2025)
This study aims, within the framework of promoting tourism in the Tipaza region, to shed light on tourism demand in the area in order to understand tourist behaviour and identify the key determinants. This is particularly relevant as Algeria was affected by the COVID-19 pandemic, which partially disrupted domestic tourism activities. These events lead researcher to consider the effectiveness of statistical methods in forecasting the recovery of tourism demand during an unexpected and volatile crisis, prompting the use of dynamic models. The study relies on a data set of monthly variables, including the number of tourists in the region (VT), the number of hotel nights (NT), the number of beds (NLT), the number of rooms (NCH), and employment (EMP) from Q1 2018 to Q4 2022, collected from the tourism sector in Tipaza. The findings indicate that seasonal employment positively contributes to tourism activity, whereas permanent employment has a negative impact. Additionally, the number of rooms plays a crucial role in determining hotel demand, as it is linked to the limited accommodation capacity during peak seasons.